2010
DOI: 10.1038/cr.2010.24
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPα regulates SIRT1 expression during adipogenesis

Abstract: SIRT1 plays an important role in adipogenesis, but how SIRT1 is regulated in adipogenesis is largely unknown. In this study, we show that both SIRT1 protein and mRNA levels were increased along with CCAAT/enhancer-binding protein α (C/EBPα) during adipocyte differentiation. C/EBPα, but not C/EBPαp30, activated SIRT1 promoter in both HeLa cells and 3T3-L1 preadipocytes. Furthermore, C/EBPα upregulated SIRT1 mRNA and protein levels in HeLa cells and increased SIRT1 expression in a p53-independent manner in Soas2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 38 publications
4
39
0
Order By: Relevance
“…It will be interesting to examine whether NAD + intermediates can enhance sirtuin activity in the hypothalamus. Besides using STACs and NAD + intermediates, sirtuins could be activated by modulating other potential regulators and signaling pathways including deleted in breast cancer 1 (DBC1) 143 , active regulator of Sirt1 (AROS) 144 , CCAAT/enhancer-binding protein α (C/EBPα) 145 , and cAMP/protein kinase A (PKA) pathway 146 . Further drug discovery targeting these regulators and signaling pathways also has a potential to open new avenues for modulating sirtuin activity.…”
Section: Mammalian Sirtuinsmentioning
confidence: 99%
“…It will be interesting to examine whether NAD + intermediates can enhance sirtuin activity in the hypothalamus. Besides using STACs and NAD + intermediates, sirtuins could be activated by modulating other potential regulators and signaling pathways including deleted in breast cancer 1 (DBC1) 143 , active regulator of Sirt1 (AROS) 144 , CCAAT/enhancer-binding protein α (C/EBPα) 145 , and cAMP/protein kinase A (PKA) pathway 146 . Further drug discovery targeting these regulators and signaling pathways also has a potential to open new avenues for modulating sirtuin activity.…”
Section: Mammalian Sirtuinsmentioning
confidence: 99%
“…Sirtuin 1 (SIRT1), a key regulator of lipid metabolism ( 96 ), is involved in attenuating adipogenesis and inducing fat mobilization ( 97,98 ). In a recent study, it was reported that apo-10 ′ -lycopenoic acid led to the increase in SIRT1 enzyme activity by treatment with this metabolite in ob/ob mice, resulting in prevention of fatty liver ( 99 ).…”
Section: Biological Activities Of Apolycopenoidsmentioning
confidence: 99%
“…Moreover, they identified a resveratrol structural analogue, combretastatin A-4, as an activator of AMPK to improve glucose metabolism in db/db mice (21). They also showed that CCAAT-enhancer-binding protein a binds to the promoter region of SIRT1 and upregulates SIRT1 expression during adipogenesis (22). In addition, Dr. Zhai's laboratory identified that SIRT1 is able to be localized in the cytoplasm and that cytoplasm-localized SIRT1 may enhance apoptosis (23).…”
Section: Nutritional Interventionmentioning
confidence: 96%